Influence of cellulose crystal plane on cellulose hydrolysis - Wenzhi, Li; Wenyu, Lu; Minghao, Li; Hao, Wu; Guoqiang, Pan (International Journal of Agricultural and Biological Engineering, 2016)
Cellulose polymerization degree and crystal plane changing are both considered to affect acid hydrolysis, however, it is uncertain to identify which one is more important. In this study, the filter paper was treated with dilute hydrochloric acid to investigate the cellulose polymerization degree changing, and cotton linter was treated with NaOH for the purpose of changing its crystal plane. Both the treated and untreated samples were hydrolyzed under the condition of 1.0 wt% dilute hydrochloric acid with solid-liquid ratio 1:40 at 140°C for 30 min to compare the hydrolysis effects. It was found that the glucose yield increased from 9.5% to 19.7% when treated with 15% NaOH at 50°C for 30 min, and new crystal planes (1-10) (1-20) appeared after alkali treatment. According to the experimental results, it is concluded that crystal plane plays a vital role in cellulose acid hydrolysis. Keywords: biomass, degree of polymerization, crystal plane, hydrolysis DOI: 10.3965/j.ijabe.20160904.2368 Citation: Li W Z, Lu W Y, Li M H, Wu H, Pan G Q. Influence of cellulose crystal plane on cellulose hydrolysis. Int J Agric & Biol Eng, 2016; 9(4): 151－158.